Phyllodesmium rudmani (Mollusca: Nudibranchia: Aeolidoidea), a new solar powered species from the Indo-West Pacific with data on its symbiosis with zooxanthellae - Burghardt, Ingo; Gosliner, Terrence M. (Zootaxa, 2006)
A new Phyllodesmium species, P. rudmani sp. nov., is described from North Sulawesi, Indonesia and from Luzon Island, the Philippines. The new species is associated with the octocoral Xenia sp. Its external morphology is similar to other Xenia associated Phyllodesmium species, except the unique morphology of the cerata, that mimic closed polyps of Xenia. The digestive glandular branching system within the cerata is similar to that of P. jakobsenae Burghardt & Wägele, 2004, a species that was found associated with the same species of Xenia and at the same locality in Indonesia as P. rudmani. The masticatory border of the jaw with a few large denticles is similar to several other species of Phyllodemium that feed on Xenia, as are the radular teeth with numerous small denticles. The lobate receptaculum seminis is similar to that described for P. magnum Rudman, 1991, whereas the remaining species have a smooth pyriform receptaculum. Behavioural notes of the new species are given and active photosynthesis due to zooxanthellae (Dinophyceae of the genus Symbiodinium) in the digestive gland was measured in situ with a Diving-PAM (Pulse Amplitude Modulated Fluorometer). Experiments with P. rudmani indicate a symbiotic relationship with zooxanthellae, at least for three weeks. These results are compared to the ones of P. jakobsenae. Histological investigation of the cerata of P. rudmani suggests relatively high efficiency of the symbiosis for the new species because of the high grade of branching of the digestive gland.